On the other shore the Atlantic worlds of Italians in South America during the Great War - Galante, John Starosta (University of Nebraska Press, 2022)
John Starosta Galante explores the presence, pull, and rejection of Italian nationalism and italianità (or Italianness) in Buenos Aires, Montevideo, and São Paulo during World War I.